2006
DOI: 10.1097/01.yco.0000238484.12023.aa
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and violence: a search for neurobiological correlates

Abstract: A better understanding of the distinctive neurobiological characteristics of this subgroup of men with schizophrenia will contribute to developing treatments tailored to their needs, to prevent antisocial behaviours and to reduce the symptoms of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…These behaviors are, however, energetically costly and individually risky, suggesting that excessive aggression may be deleterious. In humans, aggression often manifests as violent behavior with attendant costs to society, and is frequently a component of psychiatric disorders, including schizophrenia, conduct disorder, alcoholism, bipolar disorder, and Alzheimer's disease [ 1 - 4 ]. Analysis of mutations and pharmacological treatments have established that aggressive behavior is evolutionarily conserved and is modulated by the neurotransmitters serotonin, dopamine, norepinephrine, γ-aminobutyric acid, histamine and nitric oxide as well as their receptors and transporters and key enzymes in their biosynthetic pathways in mammals [ 5 ] and invertebrates [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These behaviors are, however, energetically costly and individually risky, suggesting that excessive aggression may be deleterious. In humans, aggression often manifests as violent behavior with attendant costs to society, and is frequently a component of psychiatric disorders, including schizophrenia, conduct disorder, alcoholism, bipolar disorder, and Alzheimer's disease [ 1 - 4 ]. Analysis of mutations and pharmacological treatments have established that aggressive behavior is evolutionarily conserved and is modulated by the neurotransmitters serotonin, dopamine, norepinephrine, γ-aminobutyric acid, histamine and nitric oxide as well as their receptors and transporters and key enzymes in their biosynthetic pathways in mammals [ 5 ] and invertebrates [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This proposition is based on evidence from studies that compare violent and non-violent patients with schizophrenia--only a few of which distinguish early starters (for a review see Naudts & Hodgins 2006), and from studies that compare patients with schizophrenia with and without co-occurring substance misuse disorders (for a review, see Potvin et al 2008). Results suggest that among patients with schizophrenia, those who present an early onset stable pattern of antisocial behaviour perform better on tests tapping specific executive functions (Wisconsin Card Sorting Test, Trail Making Test, WAIS, Trigram Test, Control Oral Word Association Test), more poorly on assessments of orbitofrontal functions, show fewer neurological soft signs, display larger reductions in volume of the amygdala, more structural abnormalities in the orbitofrontal system, more abnormalities of white matter in the amygdalaorbitofrontal system, and smaller reductions of the hippocampus.…”
Section: Early Start Offenders With Schizophreniamentioning
confidence: 99%
“…74 Deformities in this region are closely related to positive symptom severity and are correlated with antipsychotic dosage, 75 showing the significance of hippocampal changes to the disease course. Studies on related disorders (with adolescent onset) have found additional hippocampal abnormalities in those patients with obsessive-compulsive symptoms and antisocial violent behavior, 76,77 which highlights the relevance of hippocampal abnormalities to psychiatric disorders in general.…”
Section: Subcortical Structuresmentioning
confidence: 96%